Salvaged pages : young writers' diaries of the Holocaust - Zapruder, Alexandra (Yale University Press, 2002)
This collection of diaries, written by young people during the Holocaust, reflects a diverse range of experiences. It contains excerpts from 15 diaries, and the diarists range in age from 12-22. The accounts explore daily events, ideas and feelings.